Graceful labeling of triangular extension of complete bipartite graph - Sarbari Mitra; Soumya Bhoumik (Electronic Journal of Graph Theory and Applications (EJGTA), 2019)
For positive integers m, n, Km, n represents the complete bipartite graph. We name the graph G = Km, n ⊙ K2 as triangular extension of complete bipartite graph Km, n, since there is a triangle hanging from every vertex of Km, n. In this paper we show that G is graceful when m = n = 2ℓ, for any integer ℓ.